2016
DOI: 10.1177/1473325016633445
|View full text |Cite
|
Sign up to set email alerts
|

Supervision: A contested space for learning and decision making

Abstract: Supervision is a core activity in social work in the UK and elsewhere, widely associated with a range of positive outcomes for service users and professionals, while Public Inquiries and Serious Case Reviews have identified poor supervision as a factor in some child deaths. While there is agreement on the nature and value of 'good' supervision there are debates on the possibilities of delivering it in today's pressured, poorly resourced working environments and a lack of data on what actually happens in superv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Finally, and with a second brief detour into the social work literature, we find the work of David Saltiel (2017) speaking to our current situation as he proposes a model of supervision that is fundamentally collaborative in nature. This is due in part to the highly complex and contested space that he understands supervision to represent as both supervisor and supervisee wrestle to shape their professional identities while at the same time striving to forge individual and collective knowledge.…”
Section: Journey Through a Journalmentioning
confidence: 85%
See 2 more Smart Citations
“…Finally, and with a second brief detour into the social work literature, we find the work of David Saltiel (2017) speaking to our current situation as he proposes a model of supervision that is fundamentally collaborative in nature. This is due in part to the highly complex and contested space that he understands supervision to represent as both supervisor and supervisee wrestle to shape their professional identities while at the same time striving to forge individual and collective knowledge.…”
Section: Journey Through a Journalmentioning
confidence: 85%
“…The limited evidence that is available from the KSS CRC study offers the impression that SPOs operate somewhere between the two ends of a supervision spectrum in which professional aspirations struggling within an arena of incessant work demands. SPO clarity of role may prove interesting here as the bifurcating demands of the job require not only organisational support but assistance with the challenges of identity formation in terms of self, team, and wider organisation as aspects of this may become lost within pressured working environments (Saltier, 2017). Of note is the fact that several respondents within the current study were clearly aware and sympathetic towards the position of SPOs, reminiscent of values held since the 1970s that supervision should be a mutually beneficial process for all involved (Williamson, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These current realities require social workers to re-think and re-define their professional practices. Recent research has reported that supervision has huge significance in developing and sustaining a social worker's professional identity and their role (Saltiel, 2016). Through reflective supervision, the social worker can develop confidence through critical examination and manage the contradictions and complexity associated with their professional position.…”
Section: Original Article Theoretical Researchmentioning
confidence: 99%
“…Maintaining professional relationships is core to social work and the supervision space reveals contested and competing narratives from the supervisor, supervisee, service users, and other professionals (Saltiel, 2016). An open discussion and exploration of the social worker's professional relationships are central to reflective supervision.…”
Section: Layer Three: Relationships With Othersmentioning
confidence: 99%